PRINSIP POKOK UNTUK MENJAMIN KEPASTIAN HUKUM SERTIFIKAT HAK ATAS TANAH DALAM SISTEM PUBLIKASI PENDAFTARAN TANAH DI INDONESIA - Lilik, Warsito; Urip, Giyono (Jurnal De Jure Muhammadiyah Cirebon, 2024)
The issue of legal certainty surrounding land title certificates, a form of land registration in Indonesia, has consistently posed substantial challenges to society. This is due to the prevailing negative system of publication in Indonesia, despite the existence of certain positive elements. Nevertheless, the authenticity of certificates verifying these rights may be prone to disagreements, and the government lacks the ability to guarantee the precision of both the physical and legal details. This study encompasses normative legal research utilizing statutory sources, as well as conceptual and philosophical techniques. Due to the lack of a proactive land registration publication mechanism, people or organizations in Indonesia who possess land rights cannot now receive the research findings on the nature of legal certainty about land rights certificates. Keywords: Legal Certainty; Land Publication; Land Certificates